231k views
0 votes
Convert the equations into slope intercept form,

then identify the slope and y-intercept.


1. -x + y = 3

m=

b=

2. -4x + 2y = 6

m=

b=

3. 2x + =3

m=

b=

User Didito
by
5.6k points

1 Answer

2 votes

Answer:

1. -x + y = 3

m= 1

b= 3

2. -4x + 2y = 6

m= 2

b= 3

Explanation:

Slope intercept is form to write equation for straight line.

It is represented as y = mx+ b

where m is the slope of line

B is the y intercept (pint on y axis where the line crosses y axis)

________________________________________________

Given

1. -x + y = 3

we need to convert this line in form of y = mx+ b

-x + y = 3

to do this we have to move - x from LHS to RHS

it can be done by adding both side +x which will eleminate -x from LHS

-x + y + x = 3 + X

=>y = 3 + x

=> y = x +c

Thus comparing it with slope form line: y = mx+ b

m =1

b = 3

__________________________________________________

Given

1. -4x + 2y = 6

we need to convert this line in form of y = mx+ b

-4x + 2y = 6

to do this we have to move + 4x from LHS to RHS

it can be done by adding both side +4x which will eleminate -4x from LHS

-4x + 2y + 4x= 6 +4x

=>2y =6 +4x

Now we have to remove 2 from 2y =6 +4x

To do this we divide both side by 2 . now we have equation

=> 2y/2 =(6 +4x)/ 2 = 6/2 + 4x/2

=> y = 3 + 2x

Thus comparing it with slope form line: y = mx+ b

m = 2

b = 3

__________________________________

Third part has 2x + =3 has y missing

it can be solved similarly.

say in place of y we have my where m is coefficient of y

2x + my =3

to do this we have to move + 2x from LHS to RHS

it can be done by subtracting -2x from both side which will eleminate 2x from LHS

2x + my -2x =3 -2x

=>my =3 -2x

Now we have to remove m from my =3 -2x

To do this we divide both side by m . now we have equation

=> my/m =(3 -2x)/ m = 3/m -2x/m

=> y = 3/m - 2x/m

Thus comparing it with slope form line: y = mx+ b

m = -2/m

b = 3/m

User Yggdrasil
by
5.4k points